2017
DOI: 10.18203/2394-6040.ijcmph20174811
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality in Ghana: an exploration of partners’ perception about factors that contributed to their wife’s death

Abstract: Background: Many programmes were put in place internationally and locally to curtail the menace of maternal mortality, but little achievement has been made in certain parts of the world, particularly in sub-Saharan Africa. A number of literatures exist, which investigate into the predisposing factors of maternal mortality in Ghana, however, no published evidence as the time of conducting this study explore the perception of men with respect to maternal mortality. This study aims to explore the perceptions of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Studies in rural and urban Nigeria reported that policymakers, elders and other community members perceived malaria or fever as the most common medical ailments leading to a maternal death [45, 49]. Policymakers and male partners in sub-Saharan Africa believed excessive bleeding was the most common direct cause of women’s maternal death [49, 50], which is similar to narratives about bleeding in this study. Non-medical reasons identified by elders in this study include unavailability of facility services, and poor awareness and negligence.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Studies in rural and urban Nigeria reported that policymakers, elders and other community members perceived malaria or fever as the most common medical ailments leading to a maternal death [45, 49]. Policymakers and male partners in sub-Saharan Africa believed excessive bleeding was the most common direct cause of women’s maternal death [49, 50], which is similar to narratives about bleeding in this study. Non-medical reasons identified by elders in this study include unavailability of facility services, and poor awareness and negligence.…”
Section: Discussionsupporting
confidence: 76%
“…These reasons are related to non-medical determinants of maternal deaths identified in the literature, including social, economic, and cultural factors [45, 49, 5154], as well as political factors, healthcare system coordination, health services provision, community contexts, and demographic characteristics [49, 55]. Delays in reaching health facilities, delays in receiving care, and poorly skilled health attendants were also held responsible for high maternal mortality rates [50, 54, 56]. A cross-sectional study in Nigeria reported that men blame women’s failure to use FP, emergency, antenatal, and delivery care services for their deaths [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ghana Health Service (GHS) has directed that all referrals be accompanied by fully completed referral forms [ 9 ]. This is essential in maternity cases considering the severity of issues that prompts maternal referrals, including haemorrhage and foetal distress [ 10 , 11 ]. Nearly all lower level facilities in Ghana refer maternal complications to higher levels of healthcare [ 12 ].…”
Section: Introductionmentioning
confidence: 99%